Laminated Veneers with Stratified Feldspathic Ceramics - Henrique Tuzzolo Neto; Wagner Ferreira do Nascimento; Larissa Erly; Rodrigo Alves Ribeiro; Jorge de Sá Barbosa; Jessica Mina Zambrana; Lariça Barbosa Raimundo; Cristiane da Silva Mendes; Ivan Pereira da Silva; Alfredo Mikail Melo Mesquita; Daniela Miranda Richarte de Andrade Salgado; Claudio Costa (Case Reports in Dentistry)
Currently, there has been a growing demand for restorations of anterior teeth in the routine of doctors in dental offices. With advances in adhesive technology and good properties of the available ceramics, the use of ceramic veneers has been offered as a treatment option for cases where teeth have minor color changes and shape and position changes. Through careful treatment planning, it is possible to conservatively use ceramic veneers in the treatments, applying techniques with minimal wear of the teeth and obtaining excellent aesthetic results with mechanical stability and biocompatibility with the periodontal tissues and clinical longevity. This clinical case report was used to design the digital smile, which guided the production of the diagnostic waxing of the superior model. Silicone guides were then made to create the mock-up, orienting enamel/dentin wear and assisting the preparation of the crowns with bis-acryl resin. When the wear was finished, the gingival separation was performed using the double-thread technique. In the molding process, the second wire was withdrawn and the molding material flowed into the gingival groove, copying the terminal region. After analysis of the quality of the impression, the temporary crowns were made with bis-acryl resin, using the guide. The color of the cementing agent was chosen using a glycerin-based compound which simulates the final color of the cement. After two hours of drying, two different layers of silane were applied for 60 seconds. After the preparation of the piece, gingival isolation and separation were done. The dental substrate was degreased with detergent solution and conditioned with 37% phosphoric acid for 15 seconds and then washed for 45 seconds for subsequent drying, leaving the substrate moistened. The adhesive system was applied for 30 seconds, waiting for the adhesive to penetrate into the conditioned dentinal tubules. A light air jet was applied, and then each tooth was photopolymerized for 30 seconds. The resin cement was placed inside the pieces and placed in position and photopolymerized. The excess cement was removed; after a layer of glycerin in the cervical region, aiming to block the entry of oxygen and polishing was performed. The purpose of this case report was to describe a sequence of clinical steps, from planning to cementation, in a case of aesthetic correction using feldspathic ceramic veneers.